Trace metals distribution in fish tissues (Cyprinus carpio and Barbus luteus) and sediments from Al-Msab Alamm River near the center of Al-Nassiriya city. - Y. ALKhafaji, Basim (University of Thi-Qar Journal of Science, 2012)
The present study was conducted to investigate the concentration and distribution of four trace metals cadmium, cobalt, copper and lead, in exchangeable and residual phases of the sediment in Al-Masab Alamm and tissues (gills, liver and muscle) of two important commercial species of fish (Cyprinus carpio and Barbus luteus) during summer season 2010. Also the present study include some physical and chemical properties of this ecosystem. The results showed clear coordination between air and water temperature in all study locations. Air and water temperatures ranged between (34.5-39.31) ºC and (26.22-32.01) ºC respectively. PH, salinity, dissolved oxygen and biological oxygen demand ranged between (7.3-8.6), (4.3-9.01) ‰, (6.0-7.70) mg/L and (2.26-3.25) mg/L respectively. Localized variations were noticed in percentages composition of sediment contents of clay, silt and sand. Total organic carbon ranged between (0.28-1.85) in study stations.The mean concentrations of Cd, Co, Cu and Pb in exchangeable and residual phases as follow Cd (4.22, 0.14), Co (12.40, 19.33), Cu (4.76, 12.71) and Pb (29.21, 1.85) µg/g dry weight respectively.The present study showed a difference in concentrations of studied metal in different tissues of fish, these concentrations varies from one species to another and the tissues of same species showed differences in concentration of studied metals. This due to the nature and the function of the tissue and ability of fish on regulating the level of the metals in their bodies during the uptake and elimination processes.